Kaidah Fiqih Hukum Keluarga Dan Penerapannya Dalam Undang-Undang Perkawinan - Fitria Agustin; Rokilah Rokilah (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The Qur'an's attention to the family is shown by the many verses that talk about family problems, from marriage problems to the problem of dividing inheritance. It is not only shown by the details of family problems regulated in it, but also by the verses that talk about various family rules. The facts that occur regarding marriage sometimes give rise to multiple interpretations among experts and the public, especially among Muslims. This article focuses on a review of Fiqh Rules or specifically Legal Rules (Qawaid al Ahkam) which are applied to resolve practical problems in Family Law. This rule classifies similar problems into one specific rule based on sources from the Koran and Hadith which are expected to make it easier to understand and resolve problems related to Family Law with normative application, namely Legislation on Marriage. This type of qualitative normative juridical research is research that refers to legal norms contained in legislation and norms that live and develop in society. The research results show that 1) The legal principles applied in Marriage law in Indonesia are the principle of monogamy, the principle of consensuality, the principle of proportionality and the principle of complete unity; 2) Fiqh rules in Islamic Family Law are applied in the Marriage Law with the aim of solving community problems within the scope of family and marriage law.